Elementi transporta žarkov nabitih delcev - Kuhar, Kristijan (Matrika, 2014)
The article discusses the basic methods of management Beamline in accelerators. Starting from the Lorentz force I introduce the concept of ideal path and the equations of motion of particles in the transverse directions around it. I present a matrix formalism for the transformation of the beam in the presence of a magnetic field and briefly describe the accelerator SuperKEKB.
Keywords: accelerators; Lorentz force; Lorentzova sila; magnetic field; magnetno polje; pospeševalniki